Scenarios : Aguirre, the Wrath of God; Every Man for Himself and God Against All; Land of Silence and Darkness; Fitzcarraldo - Herzog, Werner, 1942- (Book collections on Project MUSE., 2017)
Werner Herzog doesn't write traditional screenplays. He writes fever dreams brimming with madness, greed, humor, and dark isolation that can shift dramatically during production--and have materialized into extraordinary masterpieces unlike anything in film today. Harnessing his vision and transcendent reality, these four pieces of long-form prose earmark a renowned filmmaker at the dawn of his career.